Teatr i taniec – koegzystencja i emancypacja - Szymajda, Joanna (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The present text evokes the various forms of coexistence between theater and dance that have developed over the course of the 20th and 21st centuries. A briefly sketched matrix of possible intersections between theater and dance outlines against historically shaped cartographies those that arise from the more recent practice of both arts. Starting from ideas and general dramaturgical or aesthetic categories (rhythm, movement, body), the ways of dialogue between the two arts are also shown on the examples coming from the field of experimental stage forms and genres (with an accent on the Polish artists) and in the scientific ground of theatrical studies, from which the dance studies are slowly separating.